Feasibility Analysis of Patchouli Farming Business In Burana Village, Tabulahan District, Mamasa Regency - Pebrianto, Erdi Olins; Ikawati; Putri, Dwi Ahrisa (Indonesian Journal of Agricultural Research, 2022)
Patchouli has begun to be widely cultivated by farmers in Burana Village with its easy cultivation and offer a promising profit. This study aims to determine whether or not it is feasible to develop a patchouli farming businessÂ  inÂ  this area. Quantitative research is used to anlyze farm costs, farming profits, farm income, return cost ratio (R/C), capital productivity (n/C) and break-even point analysis (BEP). The results showed that the average area of farmers' land is 47.22 acres, so the average cost of production on patchouli farming is Rp. 23,521,073, and the average revenue obtained is Rp. 30,486,379, then the average profit for each respondent is Rp. 6,965,306, so the R/C ratio obtained is 1.3 because the value of the R/C ratio is greater than 1, so patchouli farming is feasible. The value of Ï€/C 0.29 indicates a profitable business where each additional cost of Rp. 100 then a profit of Rp. 29 (29%). The analysis of break-even point for the production volume in patchouli farming is 53,458 kg, meaning that at 53,458 kg the patchouli business is profitable because the patchouli product number of 53,456 kg is below the average product figure of 69.998 kg. Analysis of the point of return for the cost of production in patchouli farming is Rp. 336,025 shows that it is still below the market price of Rp. 439,995, means that the patchouli business is profitable.